2022
DOI: 10.1073/pnas.2200748119
|View full text |Cite|
|
Sign up to set email alerts
|

Stress accumulation by confined ice in a temperature gradient

Abstract: When materials freeze, they often undergo damage due to ice growth. Although this damage is commonly ascribed to the volumetric expansion of water upon freezing, it is usually driven by the flow of water toward growing ice crystals that feeds their growth. The freezing of this additional water can cause a large buildup of stress. Here, we demonstrate a technique for characterizing this stress buildup with unprecedented spatial resolution. We create a stable ice–water interface in a controlled temperature gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…During in situ freezing flow in premelted films at colder locations can also occur (secondary frost heave) [38]. At short laboratory timescales the magnitude of secondary frost heave is relatively small [39] and ice lenses grow without penetrating the warmer pores [15].…”
Section: Effect Of Particle Trapping On Frost Heavementioning
confidence: 99%
“…During in situ freezing flow in premelted films at colder locations can also occur (secondary frost heave) [38]. At short laboratory timescales the magnitude of secondary frost heave is relatively small [39] and ice lenses grow without penetrating the warmer pores [15].…”
Section: Effect Of Particle Trapping On Frost Heavementioning
confidence: 99%
“…The freezing temperature T f of the soil is given by the Clapeyron equation [37,38], and in general there exists a region of soil of depth d f between the freezing front and the 0 • C isotherm.…”
Section: Thin Interface Approximationmentioning
confidence: 99%
“…Numerical simulations by O'Neill and Miller [49], Fowler et al [33,34] and Rempel [51] show that after an initial transient period the heave varies approximately linearly with time, in qualitative agreement with the high-overburden pressure h(t) data in figure 3. Gerber et al [38] have shown recently that experimental flow rates during secondary frost heave in a model soil are relatively slow, and mechanisms for increasing the flow rates were discussed. One possibility mentioned was the presence of hydrogels or other colloidal media, which allow larger amounts of unfrozen water to be present at sub-zero temperatures.…”
Section: Secondary Frost Heavementioning
confidence: 99%
“…Now, water can flow away as ice grows, preventing any pressure build-up during ice's initial growth. However, if the ice is below its freezing temperature, and in contact with an unfrozen supply of water, it will subsequently suck water back into the pore, causing the ice to grow [6,9,10]. Then, the ice can push open the pore, causing pressure to build up with a maximum pressure of about 1 MPa per degree of undercooling [1, 5,9,[11][12][13][14].…”
mentioning
confidence: 99%
“…However, if the ice is below its freezing temperature, and in contact with an unfrozen supply of water, it will subsequently suck water back into the pore, causing the ice to grow [6,9,10]. Then, the ice can push open the pore, causing pressure to build up with a maximum pressure of about 1 MPa per degree of undercooling [1, 5,9,[11][12][13][14]. Importantly, the expansion of the pore due to cryosuction can theoretically be unbounded, provided enough unfrozen water is available.…”
mentioning
confidence: 99%